Editorial: MAFLD and outcome prediction. Issue 6 (4th March 2022) - Muthiah, Mark D.; Lim, Seng Gee
LINKED CONTENT: This article is linked to Decraecker et al papers. To view these articles, visit https://doi.org/10.1111/apt.16760 and https://doi.org/10.1111/apt.16793